2018
DOI: 10.1111/cote.12382
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ultraviolet‐curable water‐borne polyurethane acrylate binder concentration on the printing performance of synthetic leather

Abstract: In this paper, synthetic leather samples were screen printed with pigmented pastes including two types of photoinitiators and three different concentrations of ultraviolet (UV)‐curable water‐borne polyurethane acrylate binder. The curing process was conducted under different combinations of lamps (gallium, mercury, gallium/mercury and gallium/gallium/mercury) at three power levels. Abrasion resistance, crock fastness, hardness and colour strength were investigated. Chemical changes in the clear and pigmented f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…The printing performance results (Table 9) of PEG-C binder, synthesized with PEG 2000 polyol and low DMPA amount (4.89 wt. %), which provided the best abrasion resistance and crock fastness values, were compared with those of a commercial binder as reported in our previous studies (Baysal et al , 2018a, b). According to results, samples printed with synthesized binder showed lower crock fastness and abrasion resistance values than those of commercial binder.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The printing performance results (Table 9) of PEG-C binder, synthesized with PEG 2000 polyol and low DMPA amount (4.89 wt. %), which provided the best abrasion resistance and crock fastness values, were compared with those of a commercial binder as reported in our previous studies (Baysal et al , 2018a, b). According to results, samples printed with synthesized binder showed lower crock fastness and abrasion resistance values than those of commercial binder.…”
Section: Resultsmentioning
confidence: 99%
“…UV-curable printing pastes (solid content: 46%), including commercial/synthesized WPUA binder, equal photoinitiator (Omnirad® 819 DW and Omnirad® 500) ratio (1:1), pigment concentration of 3% and other additives, e.g. wetting agent, defoamer, thickener and ammonia solution, were prepared as reported in our previous studies (Baysal et al , 2018a, b). The printing formulations were prepared as given in Table 4.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we reported on the effect of the water-borne polyurethane acrylate binder concentration and photoinitiator ratio on the UV printing performance of synthetic leather [20,21]. In the current study, we aimed to determine the effect of different colour pigments on the UV printing performance of synthetic leather samples.…”
Section: Introductionmentioning
confidence: 95%
“…In a recent study, Baysal et al examined the effect of binder concentration on abrasion resistance, crock fastness and K/S of pigment-printed and UV-cured synthetic leather samples. The results showed that it was possible to obtain high quality and durable pigment prints on synthetic leather sample using a UV-curable formulation including an equal ratio of photoinitiators (Omnirad 819 DW and Omnirad 500) with a binder concentration of 46% [22].…”
Section: Introductionmentioning
confidence: 99%